Coordinated innate and T-cell immune responses in mild COVID-19 patients from household contacts of COVID-19 cases during the first pandemic wave - Aiello, Alessandra; Grossi, Adriano; Meschi, Silvia; Meledandri, Marcello; Vanini, Valentina; Petrone, Linda; Casetti, Rita; Cuzzi, Gilda; Salmi, Andrea; Altera, Anna Maria; Pierelli, Luca; Gualano, Gina; et al. (Frontiers in Immunology, 2022)
Objective: To better define the immunopathogenesis of COVID-19, the present study aims to characterize the early immune responses to SARS-CoV-2 infection in household contacts of COVID-19 cases. In particular, innate, T- and B-cell specific responses were evaluated over time. Methods: Household contacts of COVID-19 cases screened for SARS‑CoV‑2 infection by nasopharyngeal swab for surveillance purposes were enrolled (T0, n=42). Of these, 28 subjects returned for a follow-up test (T1). The innate response was assessed by detecting a panel of soluble factors by multiplex-technology in plasma samples. Cell-mediated response was evaluated by measuring interferon (IFN)-γ levels by ELISA in plasma harvested from whole-blood stimulated with SARS‑CoV‑2 peptide pools, including spike (S), nucleocapsid (N) and membrane (M) proteins. The serological response was assessed by quantifying anti-Receptor-Binding-Domain (RBD), anti-Nucleocapsid (N), whole virus indirect immunofluorescence, and neutralizing antibodies. Results: At T0, higher levels of plasmatic IFN-α, IL-1ra, MCP-1 and IP-10, and lower levels of IL-1β, IL-9, MIP-1β and RANTES were observed in subjects with positive swab compared to individuals with a negative one (p<0.05). Plasmatic IFN-α was the only cytokine detectable in subjects with positive SARS-CoV-2 swabs with high accuracy for swab score positivity (0.93, p<0.0001). Among subjects with positive swabs, significant negative correlations were found among the RT-PCR cycle threshold values reported for genes S and N and IFN-α or IP-10 levels. At T0, the IFN-γ T-cell specific response was detected in 50% (5/10) of subjects with positive swab, while anti-RBD/anti-N antibodies showed a positivity rate of 10% (1/10). At T1, the IFN-γ T-cell specific response was detected in most of the confirmed-infection subjects (77.8%, 7/9), whereas the serological response was still observed in a minority of them (44.4%, 4/9). Overall, the swab test showed a moderate concordance with the T-cell response (78.6%, k=0.467), and a scarce concordance with the serological one (72.9%, k=0.194). Conclusions: Plasmatic IFN-α and the IFN-γ T-cell specific response appear early even in the absence of seroconversion, and show a greater positivity rate than the serological response in household contacts with positive swab.